2022
DOI: 10.5182/jaie.33.105
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cobalt Oxide Nanocomposite Catalyst from Cobalt Aluminum Layered Double Hydroxide Precursor Towards Aerobic Alcohol Oxidation

Abstract: The A n− /CoAl LDH_x precursors with various interlayer anions (A n− ) and Co 2+ to Al 3+ ratios (x) were successfully synthesized using the co-precipitation method under alkaline conditions. The XRD profiles of the as-prepared A n− /CoAl LDH_x resembles the typical pattern of hydrotalcite materials without any presence of impurities. The TG-DTA analysis revealed that different types of interlayer anions led to the formation of LDH with different thermal behavior. The cobalt aluminum oxide nanocomposite, A n− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…12_CuAl LDH@α‐Al 2 O 3 possessed the characteristics of a layered structure with diffraction peaks corresponding to the (003) and (006) planes at 2θ values of 11.7° and 23.6°, respectively (Figure 2(a)), as well as diffraction peaks belonging to α‐Al 2 O 3 (Figure 2(a)). The basal spacing of the (003) plane ( d 003 ) of 12_CuAl LDH@α‐Al 2 O 3 was 0.76 nm, which is characteristic of CO 3 2− ‐intercalated LDH materials [12,13] . Notably, the crystallite size of the (003) plane ( D 003 ) of 12_CuAl LDH@α‐Al 2 O 3 , calculated from the Debye–Scherer equation, was 26.6 nm (unsupported CuAl LDH was 27.8 nm).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…12_CuAl LDH@α‐Al 2 O 3 possessed the characteristics of a layered structure with diffraction peaks corresponding to the (003) and (006) planes at 2θ values of 11.7° and 23.6°, respectively (Figure 2(a)), as well as diffraction peaks belonging to α‐Al 2 O 3 (Figure 2(a)). The basal spacing of the (003) plane ( d 003 ) of 12_CuAl LDH@α‐Al 2 O 3 was 0.76 nm, which is characteristic of CO 3 2− ‐intercalated LDH materials [12,13] . Notably, the crystallite size of the (003) plane ( D 003 ) of 12_CuAl LDH@α‐Al 2 O 3 , calculated from the Debye–Scherer equation, was 26.6 nm (unsupported CuAl LDH was 27.8 nm).…”
Section: Resultsmentioning
confidence: 95%
“…12_CuAl LDH@α-Al 2 O 3 possessed the characteristics of a layered structure with diffraction peaks corresponding to the (003) and ( 006 (003) plane (d 003 ) of 12_CuAl LDH@α-Al 2 O 3 was 0.76 nm, which is characteristic of CO 3 2À -intercalated LDH materials. [12,13] Notably, the crystallite size of the (003) plane (D 003 ) of 12_CuAl LDH@α-Al 2 O 3 , calculated from the Debye-Scherer equation, was 26.6 nm (unsupported CuAl LDH was 27.8 nm). From the SEM images and XRD results, it can be concluded that the CO 3 2À / CuAl LDH was successfully supported on α-Al 2 O 3 with high dispersion.…”
Section: Catalyst Preparation and Characterizationmentioning
confidence: 99%